Testing eye temperature assessed with infrared thermography to evaluate stress in meat goats raised in a semi-intensive farming system: A pilot study - Bartolomé Medina, Ester (2019)
The Blanca Serrana goat is selected for meat production and usually raised in an extensive farm system. The meat goat industry is getting bigger in Spain, evolving to more intensive farming systems. The negative influence of stress produced by daily management on animal welfare is even bigger in these animals as they are not used to getting so close to humans. Eye temperature has recently appeared as an appropriate and noninvasive tool for welfare assessment in cattle, but no previous studies have been developed in goats. Thus, the main aim of this pilot study was to test eye temperature as a noninvasive tool to explore stress levels associated with a semi-intensive farming system for meat goats in comparison with the standard measurements of stress. For that, 24 Blanca Serrana goats were used. Heart rate (HR), respiratory rate (RR) and eye temperature (ET), assessed with infrared thermography samples, were collected just before and just after a stressful situation created to check how the routine management of semi-intensive farming systems affected this species. A factorial ANOVA, least square means and Scheffe post hoc comparison analyses found statistically significant differences due to the stress test moment for RR (p<0:05) and ET (p<0:001) with higher values shown after the stress test than before it. Differences due to age were found just for HR (p<0:05) and RR (p<0:01) stress parameters, with kids showing higher results than adults. Pearson correlations between HR, RR and ET parameters showed a medium-high positive correlation of 0.56 between RR and ET. Thus, ET appears as an appropriate and noninvasive tool to explore stress levels associated with a semiintensive farming system for meat goats.